The Use of Instructional Media in Improving Student's Skill in Essay Writing Through Blended Learning Platform - Handoko Handoko; Rabbi Antaridha (Masyarakat Linguistik Indonesia Universitas Andalas, 2019)
The research focuses on the use of instructional media in the blended learning platform to improve students' ability in writing essays. The implementation of blended learning is carried out in three cycles: brainstorming, drafting, and final writing. At the end of each cycle, there is an evaluation to find out the progress of the learning. Feedback is given from the evaluation results to overcome problems that arise in the previous cycle. The subjects of the research are students of Universitas Andalas who divided as control class and experimental class. The purpose of this study is (a) short-term; To help overcome student problems and improve their ability to write essays in English (b) long-term is to provide a basis for learning models of English writing essays at universities. The pretest indicates that 59% of participants from the control class have a low score (below 60) while in experimental class, about 60% of participants get a score below 60. The result of the research shows significant improvement in essay writing performance with an average score of post-test 76.35. By using the t-test can be seen the significance value of 0.06> 0.05, which indicates that the use of instructional media in the blended learning platform can improve students performance in writing an essay.